New technologies for customizing products for people with special necessities: project FASHION-ABLE. Issue 7 (3rd July 2017) - Durá-Gil, Juan V.; Ballester-Fernández, Alfredo; Cavallaro, Marco; Chiodi, Andrea; Ballarino, Andrea; Brondi, Carlo; von Arnim, Volkmar; Stellmach, Dieter
Abstract : Mass-customization of wearable products are offered as a higher added value to the broad public and have to compete with ready-to-wear offer. However, people with specific requirements are not covered by the current mass-customised products. This is the case of the elderly, disabled, diabetic and obese population groups when wearing textiles, clothing, footwear and textile-based orthotic goods. Further, at present, available knowledge and flexibility of production equipment and machinery of small and medium-sized enterprises operating in these traditional industries (even those that already offer made-to-measure products to the mass public) is unable to respond to the individual needs among such heterogeneous groups. The FASHION-ABLE project has solved this problem with a comprehensive set of solutions.